O CONCEITO DE LIMITE NA FORMAÇÃO INICIAL DE PROFESSORES DE MATEMÁTICA: UM ESTUDO À LUZ DOS TRÊS MUNDOS DA MATEMÁTICA - Soares, Gabriel de Oliveira (2018)
This qualitative research has as general objective to analyze the limit concept of a function in a point, presented by students of two undergraduate mathematics teaching courses, as well as its strategies of solving questions, in the light of the Theory of the Three Worlds of Mathematics. Firstly, was made an analysis of the introduction of the concept of limit in Calculus textbooks, based on the theoretical framework. Then, a mapping of articles on the ideas of David Tall was done, as well as a search of dissertations and theses that were based on these ideas. In the last phase, a test on limits of functions was applied to students of mathematics teaching courses, who had already studied the discipline of Calculus I and were interviewed professors of this discipline in both courses. The analysis of the textbooks made it possible to verify that, in the introductory chapters, there is a work that advocates features of the symbolic and embodied worlds, especially the first, with some aspects of the formal world. In relation to the interviews with the teachers, they affirmed that begin with graphical examples and tables of functions values to introduce the concept and only then try to reach the formal definition, crossing the Three Worlds of Mathematics. In the test applied to the students, it was concluded that most of them use the natural language to conceptualize limit, presenting characteristics of the embodied world, with some symbolic elements, but without achieving a development compatible with the formal axiomatic world.